Relationship Between Volatile Sulfur Compounds, Mineral Content, Morphological and Molecular Characterization Of Local Garlic Genotypes (Bangladesh Journal of Botany, 2022)
This study was conducted to determine the relationship between local garlic genotypes and Taskopru garlic, cultivated in Turkey, by using volatile sulfur compounds, mineral content, molecular and morphological characterizations. Results indicated that morphological features, mineral content and volatile sulfur compounds exhibited a great diversity among the garlic genotypes. Jaccard's similarity matrix prepared using 13 SSR markers also revealed the genetic diversity among genotypes. This genetic diversity may contribute significantly to the development of new garlic cultivars. Mineral content of the garlic leaves could be used as chemotaxonomic tool for classification of the local garlic genotypes.Bangladesh J. Bot. 51(1): 147-155, 2022 (March)